Strategi Perencanaan Manajemen Hubungan Masyarakat dalam Meningkatkan Mutu Sekolah serta Membangun Peran Masyarakat dalam Lembaga Pendidikan - Maharani, Rts Rista; Utami, Hariesty Octari; Setiyadi, Bradley (Universitas Batanghari Jambi, 2024)
This research aims to describe (1) public relations management planning strategies, (2) improving school quality and (3) building the role of the community in educational institutions. This research uses a qualitative research method, literature study. The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The results of this research indicate that (1) planning, implementation and evaluation processes are needed to manage community relations with schools, (2) schools carry out community relations as a public relations work program by socializing the school's image, and (3) evaluation of these activities is carried out in implementation. Future public relations will be carried out by involving and including the participation of parents, the community and other educational institutions to be able to establish collaborative activities and educational collaboration through school public relations information and communication.